Clinical aspects of electroporation - Kee, Stephen T.; Gehl, Julie; Lee, Edward W. (Springer, 2011)
Electroporation is the forefront in tumor ablation. This book presents the basic principles and clinical applications of electroporation, including the latest research results and patient data. A comprehensive approach to the basic science behind the development of this ground-breaking technique and its introduction into clinical practice, the book discusses the entire spectrum of currently available reversible treatments, the emerging irreversible applications, and their impact on patient care. Clinical Aspects of Electroporation is the first bookintended for cliniciansonthis extremely important and rapidly developing field.